Application of GIS and Criminal Legal Aspects for Protecting Land Resources in Ukraine - Shulha, A.; Pavlykivskyi, V.; Vasyliev, A.; Kondratov, D. (Journal of Environmental Accounting and Management, 2026)
The purpose is to develop a theoretical model for land protection managing as an integral part of the natural environment, based on modern engineering and legal protection methods. The information and empirical base of the study is made up of statistical materials from the State Judicial Administration and other law enforcement agencies of Ukraine for 2011-2019. A statistical, comparative legal and structural-logical methods as well as an analytical review of engineering solutions to protect land resources were applied. The National Police of Ukraine statistics on offenses committed in the land relations field shows that in recent years there has been a sharp surge in crime against land resources and an increase in the number of participants in crimes. This can be explained by the imperfection of Ukrainian legislation in the field of land protection and the lack of advanced technologies implementation for the land resources protection. The study significance consists in identifying the imperfection of the criminal legislation of Ukraine in the investigated field and establishing the main signs of crimes against land resources as a criminal-legal category. Thus, the social danger of the act, its unlawfulness, guilt, the presence of a subject of the crime and a specific object of criminal law protection should be recognized as essential features of the crimes under study. It is inappropriate to single out guiltiness as an independent sign of crimes against land resources, since it logically follows from the sign of ``unlawfulness". In addition the comprehensive regional control is proposed taking into account engineering, technical and legal aspects, since Ukrainian law enforcement departments have not used the GIS aspect for crime analysis to date. The research originality consists in the proposal of the comprehensive land resources protection management based on the use of engineering and criminal legal methods, which are complementary.